Acrylonitrile-styrene-butadiene copolymer material and preparation method thereof

By using the formulation of phosphorus-based, nitrogen-based flame retardant and modified polyhedral oligosilsesquioxane and its derivative flame retardant synergist in the acrylonitrile-styrene-butadiene copolymer material, the problem of insufficient flame retardant properties and mechanical properties is solved, and higher flame retardant grades and mechanical properties are achieved.

CN119752094AActive Publication Date: 2025-04-04SHENZHEN WOER HEAT SHRINKABLE MATERIAL
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411993323.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-04
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

The flame retardant and mechanical properties of acrylonitrile-styrene-butadiene copolymer materials are poor, making it difficult to meet higher application needs.

Method used

The flame retardant and mechanical properties of the material are significantly improved through the synergistic effects of these flame retardants.

Benefits of technology

By modifying the carbon layer, ceramic barrier layer, protective film or thermally insulated coke layer formed during the combustion process by modifying the polyhedral oligosilsesquioxane and its derivative flame retardant synergist, the flame retardant properties and mechanical properties of the material are significantly improved, and the flame retardant grade and mechanical performance indicators are achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119752094A_ABST
    Figure CN119752094A_ABST
Patent Text Reader

Abstract

The invention discloses an acrylonitrile-styrene-butadiene copolymer material which comprises an acrylonitrile-styrene-butadiene copolymer, a phosphorus-based flame retardant, a nitrogen-based flame retardant, modified polyhedral oligomeric silsesquioxane and a derivative flame-retardant synergist of the modified polyhedral oligomeric silsesquioxane. The modified polyhedral oligomeric silsesquioxane and the derivative flame-retardant synergist thereof contain boron, an annular structure R2 with the carbon hydrogen ratio larger than 1 and two inorganic silicon cage cores, and the structures form a carbon layer, a ceramic barrier layer, a protective film or a heat-insulation coke layer and other protective layers in the combustion process, so that the anti-dripping effect is greatly improved, and meanwhile, the anti-dripping effect is greatly improved. Heat and oxygen transfer is isolated, combustible gas release is reduced, and the flame retardant property of the material is remarkably improved under the combined action of multiple mechanisms. Furthermore, the flame-retardant synergist of the modified polyhedral oligomeric silsesquioxane and the derivative of the modified polyhedral oligomeric silsesquioxane is matched with a phosphorus-based flame retardant for providing an acid source and a nitrogen-based flame retardant for providing a gas source to realize synergistic flame retardance, so that the flame-retardant property and the mechanical property of the acrylonitrile-styrene-butadiene copolymer material are improved while the consumption of the flame retardants is reduced. The acrylonitrile-styrene-butadiene copolymer material provided by the invention has relatively good flame retardant property and mechanical property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of materials, and in particular to an acrylonitrile-styrene-butadiene copolymer material. Background Art

[0002] Polyhedral oligomeric silsesquioxane (POSS) is a special organic amorphous material. It is a polycyclic organic monomer composed of a silicon framework and its embedded oxygen atoms. It is an inorganic-organic hybrid nanomaterial. The inorganic silicon cage core in POSS decomposes under heat to form a dense ceramic barrier layer, which isolates the release of combustible gas and the entry of external heat into the interior, thereby delaying further decomposition of the material. POSS shows great application potential in the field of flame retardants.

[0003] Acrylonitrile-styrene-butadiene copolymer (ABS resin) is a thermoplastic polymer material with high strength, good toughness and easy processing and molding. ABS resin is a terpolymer composed of acrylonitrile, butadiene and styrene. This material combines the advantages of three monomers and has excellent properties such as high surface hardness, toughness, good low-temperature impact resistance, good creep resistance, good dimensional stability, and small molding shrinkage. However, its oxygen index is only 18.33~20 (<21), which is a flammable material. This has become a major obstacle to the further promotion, application and development of ABS resin. ABS resin is easy to drip when burning, and an anti-drip agent needs to be added. However, the commonly used anti-drip agents on the market are still fluorine-containing anti-drip agents. Most of the inorganic anti-drip agents are montmorillonite, kaolin, etc., and the amount of addition needs to be large to be effective. However, after the addition of inorganic powder is large, the mechanical properties of ABS will be greatly affected. Therefore, it is very necessary to develop an acrylonitrile-styrene-butadiene copolymer material that can simultaneously improve flame retardancy and mechanical properties. Summary of the invention

[0004] In view of the above-mentioned deficiencies in the prior art, the present invention proposes an acrylonitrile-styrene-butadiene copolymer material, aiming to solve the problem of poor flame retardancy and mechanical properties of the current acrylonitrile-styrene-butadiene copolymer material.

[0005] The above object of the present invention is achieved through the following technical solutions:

[0006] In a first aspect, the present invention provides an acrylonitrile-styrene-butadiene copolymer material. The raw materials of the acrylonitrile-styrene-butadiene copolymer material, measured in parts by weight, include:

[0007] 50-70 parts of acrylonitrile-styrene-butadiene copolymer,

[0008] Phosphorus flame retardant 5-10 parts,

[0009] 5-10 parts of nitrogen flame retardant,

[0010] 2-8 parts of modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist,

[0011] Wherein, the structure of the modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist is:

[0012]

[0013] Wherein, R is a non-reactive group, such as isobutyl, isooctyl, ethyl, cyclohexyl, cyclopentyl, or phenyl, and R1 is n-propyl or phenylene;

[0014] R2 is a cyclic structure with a carbon-to-hydrogen ratio greater than 1, including at least one of a benzofuran group and a polycyclic aromatic group.

[0015] In some embodiments of the present invention, the benzofuran group includes at least one of a benzofuran group and a dibenzofuran group;

[0016] And / or, the polycyclic aromatic group includes at least one of a naphthalene ring group, an anthracene ring group, a phenanthrene ring group, an acenaphthene ring group, a fluorene ring group and a perylene ring group.

[0017] In some embodiments of the present invention, the modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist is prepared by dehydration reaction of compound 1 and compound 2 under the action of a catalyst, and the reaction route is as follows:

[0018]

[0019] In some embodiments of the present invention, the molar ratio of compound 1 to compound 2 is 2:1.

[0020] In some embodiments of the present invention, the method for preparing the modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist comprises the following steps:

[0021] Dissolving compound 1 in an organic solvent, adding an aqueous solution of compound 2 under the action of a catalyst, performing a catalytic reaction, and then washing and drying to obtain the modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist;

[0022] Wherein, the organic solvent includes at least one of alcohols, aromatic hydrocarbons, aliphatic hydrocarbons, alicyclic hydrocarbons, ethers, ketones and diol derivatives;

[0023] The catalyst includes at least one of an acidic catalyst, a metal catalyst, and a basic catalyst.

[0024] In some embodiments of the present invention, the phosphorus-based flame retardant includes at least one of phosphate ester and phosphite ester.

[0025] In some embodiments of the present invention, the phosphate flame retardant includes at least one of tris(β-chloroethyl) phosphate, tributyl phosphate, triphenyl phosphate, and dimethyl methyl phosphate; the phosphite flame retardant includes at least one of diisopropyl ether diphenyl phosphite, triisoquinoline phosphite, triphenyl phosphite, dimethyl phosphite, and diethyl phosphite.

[0026] In some embodiments of the present invention, the raw material of the acrylonitrile-styrene-butadiene copolymer material further includes at least one of a lubricant and an antioxidant; wherein, in terms of weight, the lubricant is 0.2-1 parts, and the antioxidant is 0.5-2 parts;

[0027] And / or, the nitrogen-based flame retardant includes at least one of melamine urate, melamine phosphate, melamine inorganic acid salt, dicyandiamide, and melamine.

[0028] The second aspect of the present invention provides a method for preparing the above-mentioned acrylonitrile-styrene-butadiene copolymer material, comprising the following steps: mixing the raw materials uniformly, extruding and granulating through an extruder to obtain a granular material, namely the acrylonitrile-styrene-butadiene copolymer material.

[0029] In some embodiments of the present invention, the raw material further comprises at least one of a lubricant and an antioxidant;

[0030] And / or, the extruder is a twin-screw extruder, and the processing temperatures of each temperature zone of the extruder are: zone 1 140-160°C, zone 2 170-180°C, zone 3 190-200°C, zone 4 190-200°C, zone 5 190-200°C, zone 6 190-200°C, zone 7 190-200°C, zone 8 170-190°C, die head 200-210°C, screw speed 150-170r / min.

[0031] The acrylonitrile-styrene-butadiene copolymer material of the present invention comprises acrylonitrile-styrene-butadiene copolymer, phosphorus-based flame retardant, nitrogen-based flame retardant and modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist. Since the modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist contains boron, a ring structure R2 with a carbon-to-hydrogen ratio greater than 1, and two inorganic silicon cage cores, the boron element forms boric acid during the combustion process, and the boric acid dehydrates and carbonizes the surface of the material to form a carbon layer; the two inorganic silicon cage cores decompose under heat to form a dense ceramic barrier layer, which isolates the release of combustible gas and the entry of external heat into the interior; the ring structure R2 with a carbon-to-hydrogen ratio greater than 1 has a higher carbon-to-hydrogen ratio, and the benzofuran group and the polycyclic aromatic group contain a large amount of carbon elements. A large amount of carbon elements will form a glassy protective film or an insulating coke layer during the combustion process. These protective films or coke layers can isolate the air, prevent the transfer of heat, and reduce the release of combustible gases. These structures form protective layers such as carbon layers, ceramic barrier layers, protective films or insulating coke layers during the combustion process, which greatly improve the anti-drip effect. At the same time, they isolate heat and oxygen transfer and reduce the release of combustible gases. The combined effect of multiple mechanisms significantly improves the flame retardant properties of the material. Furthermore, the flame retardant synergist of the modified polyhedral oligomeric silsesquioxane and its derivatives cooperates with the phosphorus flame retardant providing the acid source to synergistically flame retard, thereby reducing the amount of the flame retardant and improving the flame retardant and mechanical properties of the acrylonitrile-styrene-butadiene copolymer material. The acrylonitrile-styrene-butadiene copolymer material provided by the present invention has good flame retardant and mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 The molecular structure diagram of the modified POSS flame retardant synergist 1 of the present invention;

[0033] Figure 2 This is a molecular structure diagram of the modified POSS flame retardant synergist 2 of the present invention. DETAILED DESCRIPTION

[0034] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. It should be understood that the following embodiments are only used to explain the present invention and are not used to limit the present invention.

[0035] Unless defined otherwise, all technical and scientific terms used herein have the common meaning in the art to which the claimed subject matter belongs.

[0036] Polyhedral oligomeric silsesquioxane (POSS) is a special organic amorphous material. It is a polycyclic organic monomer composed of a silicon framework and its embedded oxygen atoms. It is an inorganic-organic hybrid nanomaterial. The inorganic silicon cage core in POSS decomposes under heat to form a dense ceramic barrier layer, which isolates the release of combustible gas and the entry of external heat into the interior, thereby delaying further decomposition of the material. POSS shows great application potential in the field of flame retardants.

[0037] Acrylonitrile-styrene-butadiene copolymer (ABS resin) is a thermoplastic polymer material with high strength, good toughness and easy processing and molding. ABS resin is a terpolymer composed of acrylonitrile, butadiene and styrene. This material combines the advantages of three monomers and has excellent properties such as high surface hardness, toughness, good low-temperature impact resistance, good creep resistance, good dimensional stability, and small molding shrinkage. However, its oxygen index is only 18.33~20 (<21), which is a flammable material. This has become a major obstacle to the further promotion, application and development of ABS resin. ABS resin is easy to drip when burning, and an anti-drip agent needs to be added. However, the commonly used anti-drip agents on the market are still fluorine-containing anti-drip agents. Most of the inorganic anti-drip agents are montmorillonite, kaolin, etc., and the amount of addition needs to be large to be effective. However, after the addition of inorganic powder is large, the mechanical properties of ABS will be greatly affected. Therefore, it is very necessary to develop an acrylonitrile-styrene-butadiene copolymer material that can simultaneously improve flame retardancy and mechanical properties.

[0038] In order to solve the above problems, the first aspect of the present invention provides an acrylonitrile-styrene-butadiene copolymer material. The raw materials of the acrylonitrile-styrene-butadiene copolymer material, measured in parts by weight, include:

[0039] 50-70 parts of acrylonitrile-styrene-butadiene copolymer,

[0040] Phosphorus flame retardant 5-10 parts,

[0041] 5-10 parts of nitrogen flame retardant,

[0042] 2-8 parts of modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist,

[0043] Wherein, the structure of the modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist is:

[0044]

[0045] Wherein, R is a non-reactive group, such as isobutyl, isooctyl, ethyl, cyclohexyl, cyclopentyl, or phenyl, and R1 is n-propyl or phenylene;

[0046] R2 is a cyclic structure with a carbon-to-hydrogen ratio greater than 1, including at least one of a benzofuran group and a polycyclic aromatic group.

[0047] It can be understood that the acrylonitrile-styrene-butadiene copolymer is any number between 50-70 parts, such as 50 parts, 55 parts, 60 parts, 65 parts, 70 parts, etc.; the phosphorus-based flame retardant is any number between 5-10 parts, such as 5 parts, 7 parts, 9 parts, 10 parts, etc.; the nitrogen-based flame retardant is any number between 5-10 parts, such as 5 parts, 7 parts, 9 parts, 10 parts, etc.; the modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist is any number between 2-8 parts, such as 2 parts, 4 parts, 6 parts, 8 parts, etc.

[0048] It can be understood that when R1 connected to Si in the inorganic silicon cage core is a phenylene group, since the phenylene group contains a benzene ring, the carbon-to-hydrogen ratio and the carbon content of the benzene ring are relatively high. When burned, it works together with the large amount of Si contained in the inorganic silicon cage core to further improve the flame retardant properties of the inorganic silicon cage core, thereby improving the flame retardant properties of the modified polyhedral oligomeric silsesquioxane flame retardant synergist.

[0049] It is understandable that phosphorus-based flame retardants decompose to form a non-flammable liquid film of phosphoric acid during combustion. At the same time, phosphoric acid is further dehydrated to form metaphosphoric acid, which is further polymerized to form polymetaphosphoric acid. In this process, not only does the covering layer generated by phosphoric acid have a covering effect, but also because the generated polymetaphosphoric acid is a strong acid and a strong dehydrating agent, it dehydrates the polymer and carbonizes it, changing the mode of the polymer combustion process and forming a carbon film on its surface to isolate the air, thereby exerting a stronger flame retardant effect. At the same time, phosphorus-based flame retardants are also a free radical scavenger. Using mass spectrometry technology, it is found that any phosphorus-containing compound forms PO· when the polymer burns. It can combine with hydrogen atoms in the flame area to suppress the flame. In addition, the moisture produced by phosphorus flame retardants during the flame retardant process can reduce the temperature of the condensed phase on the one hand, and dilute the concentration of combustibles in the gas phase on the other hand. The B in the modified polyhedral oligomeric silsesquioxane and its derivative synergistic flame retardant has a 2Pz empty orbital that can accept lone pairs of electrons, and can produce a synergistic effect when coordinated with phosphorus, thereby improving the flame retardant effect. In addition, the boron element forms boric acid during the combustion process, and the boric acid dehydrates and carbonizes the surface of the material to form a carbon layer; the two inorganic silicon cage cores are decomposed by heat to form a dense ceramic barrier layer, isolating the release of combustible gases and the entry of external heat into the interior; hydrocarbons The ring structure R2 with a ratio greater than 1 has a higher carbon-hydrogen ratio. The benzofuran group and the polycyclic aromatic group contain a large amount of carbon elements. A large amount of carbon elements will form a glass-like protective film or an insulating coke layer during the combustion process. These protective films or coke layers can isolate the air, prevent heat transfer, and reduce the release of combustible gases. These structures form protective layers such as carbon layers, ceramic barrier layers, protective films or insulating coke layers during the combustion process. The anti-drip effect is greatly improved. At the same time, the heat and oxygen transfer are isolated and the release of combustible gases is reduced. The combined effect of multiple mechanisms significantly improves the flame retardant properties of the material. The modified polyhedral oligomeric silsesquioxane and its derivative synergistic flame retardant contains a large amount of silicon and oxygen elements. During the combustion of the polymer, it forms phosphate with the acidic gas after the phosphorus flame retardant is burned, which promotes the reaction between the phosphorus element and the polymer, thereby quickly forming a carbon layer. The SiO2 generated after the combustion of the modified polyhedral oligomeric silsesquioxane and its derivative synergistic flame retardant is interspersed in the coke layer, similar to the role of sand in cement, making the coke layer more stable. The coke layer makes it difficult for heat to penetrate the condensed phase, preventing oxygen from entering the combustion area and the gaseous or liquid products generated by degradation from overflowing the surface of the material. The boron of the modified polyhedral oligomeric silsesquioxane and its derivative synergistic flame retardant has a 2Pz empty orbital, which can accept lone pairs of electrons and can produce a synergistic effect by coordinating with phosphorus. The synergistic effect of boron and phosphorus makes the above reaction faster. At the same time, the combustion of the nitrogen flame retardant produces a large amount of non-combustible gas, which causes the system in the molten state of the incompletely carbonized part of the ABS to foam, causing the burning polymer to produce a large number of pores.At the same time, the organic matter continues to react, dehydrate and carbonize to form inorganic matter and carbon residue. When the reaction is completed, the system gels and solidifies, and finally forms a porous foam carbon layer.

[0050] The acrylonitrile-styrene-butadiene copolymer material of the present invention comprises acrylonitrile-styrene-butadiene copolymer, phosphorus flame retardant, 5-10 parts of nitrogen flame retardant and modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist. Since the modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist contains boron, a ring structure R2 with a carbon-to-hydrogen ratio greater than 1, and two inorganic silicon cage cores, the boron element forms boric acid during the combustion process, and the boric acid dehydrates and carbonizes the surface of the material to form a carbon layer; the two inorganic silicon cage cores decompose under heat to form a dense ceramic barrier layer, which isolates the release of combustible gas and the entry of external heat into the interior; the ring structure R2 with a carbon-to-hydrogen ratio greater than 1 has a higher carbon-to-hydrogen ratio, and the benzofuran group and the polycyclic aromatic group contain a large amount of carbon elements. A large amount of carbon elements will form a glassy protective film or an insulating coke layer during the combustion process. These protective films or coke layers can isolate the air, prevent the transfer of heat, and reduce the release of combustible gases. These structures form protective layers such as carbon layers, ceramic barrier layers, protective films or insulating coke layers during the combustion process, which greatly improve the anti-drip effect. At the same time, they isolate heat and oxygen transfer and reduce the release of combustible gases. The combined effect of multiple mechanisms significantly improves the flame retardant properties of the material. Furthermore, the flame retardant synergist of the modified polyhedral oligomeric silsesquioxane and its derivatives cooperates with the phosphorus flame retardant providing the acid source to synergistically flame retard, thereby reducing the amount of the flame retardant and improving the flame retardant and mechanical properties of the acrylonitrile-styrene-butadiene copolymer material. The acrylonitrile-styrene-butadiene copolymer material provided by the present invention has good flame retardant and mechanical properties.

[0051] In some embodiments, the benzofuran group includes at least one of a benzofuran group and a dibenzofuran group.

[0052] The carbon-to-hydrogen ratio and carbon content in phenyl are both high, which can slow down the spread of flames during combustion. When the flame is removed, it can quickly extinguish itself, reducing the duration and intensity of combustion. The furan group has a high carbon content and contains oxygen elements that do not participate in combustion. The combination of the two forms a benzofuran group or dibenzofuran group that has both a high carbon-to-hydrogen ratio and a low combustion element. The two work together to form a glass-like protective film or an insulating coke layer during the combustion process. These protective films or coke layers can isolate the air and prevent heat transfer, while reducing the content of combustibles and indirectly promoting carbonization.

[0053] In some embodiments, R2 is a benzofuranyl group.

[0054] In some embodiments, the polycyclic aromatic group includes at least one of a naphthalene ring group, an anthracene ring group, a phenanthrene ring group, an acenaphthene ring group, a fluorene ring group, and a perylene ring group.

[0055] The naphthalene ring group, anthracene ring group, phenanthrene ring group, acenaphthene ring group, fluorene ring group and perylene ring group have a relatively high carbon-hydrogen ratio and contain a large amount of carbon elements, which makes it easier to form a glass-like protective film or a heat-insulating coke layer when burned.

[0056] In some embodiments, R2 is a naphthyl ring group.

[0057] In some embodiments, the modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist is prepared by dehydration reaction of compound 1 and compound 2 under the action of a catalyst, and the reaction route is as follows:

[0058]

[0059] In some embodiments, the molar ratio of compound 1 to compound 2 during the above reaction is 2:1.

[0060] The spatial structure of compound 1 polyhedral oligomeric silsesquioxane is relatively large. In the reaction, it is necessary to ensure that compound 2 has a sufficiently small spatial steric hindrance so that it can react with compound 1 to obtain compound 3 modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist. During the reaction, each compound 2 is connected to two compounds 1, that is, the molar ratio of compound 1 to compound 2 is 2:1, which ensures sufficient space for compound 3 and achieves structural stability of compound 3. Compound 2 contains two hydroxyl groups, and the two hydroxyl groups of one compound 2 are respectively combined with one amino group in two compounds 1 to undergo a dehydration reaction to obtain compound 3. The overall reaction requires a single substance, is simple to operate, and is easy to implement.

[0061] In some embodiments, compound 1 is aminopropyl heptaisobutyl caged polysilsesquioxane.

[0062] In some embodiments, compound 1 is aminophenyl heptaisobutyl caged polysilsesquioxane.

[0063] In some embodiments, compound 2 is benzo[B]naphtho[2,3-D]furan-2-hydroxyboronic acid.

[0064] In some embodiments, compound 2 is dibenzofuran-3-boronic acid.

[0065] In some embodiments, the structural formula of compound 3 is:

[0066]

[0067] The following is designated as modified POSS flame retardant synergist 1.

[0068] In some embodiments, the structural formula of compound 3 is:

[0069]

[0070] The following is designated as modified POSS flame retardant synergist 2.

[0071] In some embodiments, the preparation method of compound 3 comprises the following steps:

[0072] Compound 1 is dissolved in an organic solvent, and an aqueous solution of compound 2 is added under the action of a catalyst, and the mixture is subjected to a catalytic reaction, and then washed and dried to obtain compound 3;

[0073] Wherein, the organic solvent includes at least one of alcohols, aromatic hydrocarbons, aliphatic hydrocarbons, alicyclic hydrocarbons, ethers, ketones and diol derivatives;

[0074] The catalyst includes at least one of an acidic catalyst, a metal catalyst, and a basic catalyst.

[0075] In some embodiments, the catalyst is acetic acid.

[0076] In some embodiments, the solvent is ethanol.

[0077] In some embodiments, the phosphorus-based flame retardant includes at least one of phosphate ester and phosphite ester.

[0078] In some embodiments, the phosphate flame retardant includes at least one of tris(β-chloroethyl) phosphate, tributyl phosphate, triphenyl phosphate, and dimethyl methyl phosphate; the phosphite flame retardant includes at least one of diisopropyl ether diphenyl phosphite, triisoquinoline phosphite, triphenyl phosphite, dimethyl phosphite, and diethyl phosphite.

[0079] In some embodiments, the nitrogen-based flame retardant includes at least one of melamine urate, melamine phosphate, melamine inorganic acid salt, dicyandiamide, and melamine.

[0080] In some embodiments, the raw material of the acrylonitrile-styrene-butadiene copolymer material further includes at least one of a lubricant and an antioxidant; wherein, based on the raw materials in parts by weight, the lubricant comprises 0.2-1 parts, and the antioxidant comprises 0.5-2 parts.

[0081] In some embodiments, the lubricant includes but is not limited to PTFE powder, zinc stearate, magnesium stearate, silicone, calcium stearate or ethylene bis stearamide. By adding a lubricant, it is beneficial to promote the mixing of various raw materials to be more uniform, while improving the fluidity of the polymer resin, reducing the friction coefficient, making the surface of the product smoother, improving processing efficiency, and improving the transparency and gloss of the plastic. The type of lubricant is not limited here, and those skilled in the art can select it according to actual needs.

[0082] In some embodiments, the antioxidant includes but is not limited to asymmetric hindered phenol antioxidants, aromatic amine antioxidants, thioether antioxidants, and phosphite antioxidants. Hindered phenol antioxidants include but are not limited to antioxidant 1010 (pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate), BHT (2,6-di-tert-butyl-p-cresol), antioxidant 1076 (β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate); aromatic amine antioxidants include but are not limited to diphenylamine, p-phenylenediamine and dihydroquinoline and its derivatives or polymers, such as antioxidant 445 (4,4'-bis(α.α- The antioxidants include, but are not limited to, dimethylbenzyl)diphenylamine); thioether antioxidants include, but are not limited to, DLTP (dilauryl thiodipropionate), DSTDP (distearate thiodipropionate), and DSTP (octadecyl thiodipropionate); phosphite antioxidants include, but are not limited to, antioxidant 168 (tris[2.4-di-tert-butylphenyl]phosphite), antioxidant 618 (pentaerythritol diphosphite distearyl), and antioxidant 626 (bis[2.4-di-tert-butylphenyl]pentaerythritol diphosphite). By adding antioxidants, the antioxidant properties and aging resistance of polymer materials are beneficial, and the service life of polymer materials is extended. The types of antioxidants are not limited here, and those skilled in the art can choose according to actual needs.

[0083] The second aspect of the present invention provides a method for preparing the above-mentioned acrylonitrile-styrene-butadiene copolymer material, comprising the following steps: mixing the raw materials uniformly, extruding and granulating through an extruder to obtain a granular material, namely the acrylonitrile-styrene-butadiene copolymer material.

[0084] In some embodiments, the raw material further comprises at least one of a lubricant and an antioxidant;

[0085] And / or, the extruder is a twin-screw extruder, and the processing temperatures of each temperature zone of the extruder are: zone 1 140-160°C, zone 2 170-180°C, zone 3 190-200°C, zone 4 190-200°C, zone 5 190-200°C, zone 6 190-200°C, zone 7 190-200°C, zone 8 170-190°C, die head 200-210°C, screw speed 150-170r / min.

[0086] The content of the present invention is explained below through specific examples and data.

[0087] The information of the raw materials involved in the specific implementation is shown in Table 1:

[0088] Table 1 Information of raw materials of Examples and Comparative Examples

[0089]

[0090]

[0091] Preparation method of modified POSS flame retardant synergist 1

[0092] 2 mol of aminopropyl heptaisobutyl caged polysilsesquioxane was dissolved in 100 mL of tetrahydrofuran solution, 0.2 mol of acetic acid catalyst was added to the solution, and 1 mol of benzo[B]naphtho[2,3-D]furan-2-hydroxyboric acid was added under stirring. The reaction was stirred for 2-4 hours, and the reaction was stopped. The mixture was evaporated under reduced pressure, washed with water, and dried to obtain benzo[B]naphtho[2,3-D]furan-2-hydroxyboric acid modified aminopropyl heptaisobutyl caged polysilsesquioxane, i.e., modified POSS flame retardant synergist 1.

[0093] Preparation method of modified POSS flame retardant synergist 2

[0094] 2 mol of aminopropyl heptaisobutyl caged polysilsesquioxane was dissolved in 100 mL of tetrahydrofuran solution, 0.2 mol of acetic acid catalyst was added to the solution, and 1 mol of dibenzofuran-3-boric acid was added under stirring. The reaction was stirred for 2-4 hours, and the reaction was stopped. The mixture was evaporated under reduced pressure, washed with water, and dried to obtain dibenzofuran-3-boric acid-modified aminopropyl heptaisobutyl caged polysilsesquioxane, i.e., modified POSS flame retardant synergist 2.

[0095] Preparation method of modified POSS flame retardant synergist 3

[0096] 2 mol of aminopropyl heptaisobutyl caged polysilsesquioxane was dissolved in 100 mL of tetrahydrofuran solution, 0.2 mol of acetic acid catalyst was added to the solution, and 1 mol of methylboric acid was added under stirring. The reaction was stirred for 2-4 hours, and the reaction was stopped. The mixture was evaporated under reduced pressure, washed with water, and dried to obtain methylboric acid-modified aminopropyl heptaisobutyl caged polysilsesquioxane, i.e., modified POSS flame retardant synergist 3.

[0097] Preparation method of modified POSS flame retardant synergist 4

[0098] 2 mol of aminopropyl heptaisobutyl caged polysilsesquioxane was dissolved in 100 mL of tetrahydrofuran solution, 0.2 mol of acetic acid catalyst was added to the solution, and 1 mol of phenylboric acid was added under stirring. The reaction was stirred for 2-4 hours, and the reaction was stopped. The mixture was evaporated under reduced pressure, washed with water, and dried to obtain phenylboronic acid-modified aminopropyl heptaisobutyl caged polysilsesquioxane, i.e., modified POSS flame retardant synergist 4.

[0099] Embodiment 1:

[0100] Please refer to Table 1 and Table 2. This embodiment includes the following raw materials in parts by weight:

[0101] ABS resin 70 parts;

[0102] TCP 5 copies;

[0103] MCA 10 copies

[0104] 15 parts of modified POSS flame retardant synergist;

[0105] PE wax 0.5 parts;

[0106] Antioxidant 10100.5 parts;

[0107] The preparation method is:

[0108] ABS resin, TCP, MCA, modified POSS flame retardant synergist 1 and PE wax antioxidant 1010 were weighed by weight, mixed in a high mixer, and then fed into a twin-screw granulation unit. Extrusion granulation was carried out under the conditions that the temperatures of zones 1 to 8 of the extruder were 150°C, 180°C, 190°C, 200°C, 200°C, 200°C, 180°C, respectively, the head temperature was 200°C, and the screw speed was 160r / min to obtain an acrylonitrile-styrene-butadiene copolymer material.

[0109] Embodiment 2:

[0110] Please refer to Table 1 and Table 2. This embodiment includes the following raw materials in parts by weight:

[0111] ABS resin 50 parts;

[0112] TCP 8 copies;

[0113] MCA 5 copies

[0114] 18 parts of modified POSS flame retardant synergist;

[0115] PE wax 0.5 parts;

[0116] Antioxidant 10100.5 parts;

[0117] The preparation method is basically the same as that of Example 1, except that the ingredients and portions of the raw material components are different, see Table 1 and Table 2.

[0118] Embodiment 3:

[0119] Please refer to Table 1 and Table 2. This embodiment includes the following raw materials in parts by weight:

[0120] ABS resin 70 parts;

[0121] TCP 5 copies;

[0122] MCA 8 copies

[0123] 12 parts of modified POSS flame retardant synergist;

[0124] PE wax 0.5 parts;

[0125] Antioxidant 10100.5 parts;

[0126] The preparation method is basically the same as that of Example 1, except that the ingredients and portions of the raw material components are different, see Table 1 and Table 2.

[0127] Embodiment 4:

[0128] Please refer to Table 1 and Table 2. This embodiment includes the following raw materials in parts by weight:

[0129] ABS resin 60 parts;

[0130] TCP 10 copies;

[0131] MCA 10 copies

[0132] 15 parts of modified POSS flame retardant synergist;

[0133] PE wax 0.5 parts;

[0134] Antioxidant 10100.5 parts;

[0135] The preparation method is basically the same as that of Example 1, except that the ingredients and portions of the raw material components are different, see Table 1 and Table 2.

[0136] Embodiment 5:

[0137] Please refer to Table 1 and Table 2. This embodiment includes the following raw materials in parts by weight:

[0138] ABS resin 60 parts;

[0139] TCP 8 copies;

[0140] MCA 8 copies

[0141] 15 parts of modified POSS flame retardant synergist;

[0142] PE wax 0.5 parts;

[0143] Antioxidant 10100.5 parts;

[0144] The preparation method is basically the same as that of Example 1, except that the ingredients and portions of the raw material components are different, see Table 1 and Table 2.

[0145] Embodiment 6:

[0146] Please refer to Table 1 and Table 2. This example includes the following raw materials in parts by weight:

[0147] ABS resin 60 parts;

[0148] TCP 8 copies;

[0149] MCA 8 copies

[0150] 25 parts of modified POSS flame retardant synergist;

[0151] PE wax 0.5 parts;

[0152] Antioxidant 10100.5 parts;

[0153] The preparation method is basically the same as that of Example 1, except that the ingredients and portions of the raw material components are different, see Table 1 and Table 2.

[0154] Comparative Example 1:

[0155] Please refer to Table 1 and Table 2. This comparative example includes the following raw materials in parts by weight:

[0156] ABS resin 60 parts;

[0157] TCP 6 copies;

[0158] MCA 8 copies

[0159] 110 parts of modified POSS flame retardant synergist;

[0160] PE wax 0.5 parts;

[0161] Antioxidant 10100.5 parts;

[0162] The preparation method is basically the same as that of Example 1, except that the ingredients and portions of the raw material components are different, see Table 1 and Table 2.

[0163] Comparative Example 2:

[0164] Please refer to Table 1 and Table 2. This comparative example includes the following raw materials in parts by weight:

[0165] ABS resin 60 parts;

[0166] TCP 13;

[0167] MCA 8 copies

[0168] PE wax 0.5 parts;

[0169] Antioxidant 10100.5 parts;

[0170] The preparation method is basically the same as that of Example 1, except that the ingredients and portions of the raw material components are different, see Table 1 and Table 2.

[0171] Comparative Example 3:

[0172] Please refer to Table 1 and Table 2. This comparative example includes the following raw materials in parts by weight:

[0173] ABS resin 60 parts;

[0174] MCA 16 copies

[0175] 15 parts of modified POSS flame retardant synergist;

[0176] PE wax 0.5 parts;

[0177] Antioxidant 10100.5 parts;

[0178] The preparation method is basically the same as that of Example 1, except that the ingredients and portions of the raw material components are different, see Table 1 and Table 2.

[0179] Comparative Example 4:

[0180] Please refer to Table 1 and Table 2. This comparative example includes the following raw materials in parts by weight:

[0181] ABS resin 60 parts;

[0182] TCP 16 copies;

[0183] 15 parts of modified POSS flame retardant synergist;

[0184] PE wax 0.5 parts;

[0185] Antioxidant 10100.5 parts;

[0186] The preparation method is basically the same as that of Example 1, except that the ingredients and portions of the raw material components are different, see Table 1 and Table 2.

[0187] Comparative Example 5:

[0188] Please refer to Table 1 and Table 2. This comparative example includes the following raw materials in parts by weight:

[0189] ABS resin 60 parts;

[0190] 121 parts of modified POSS flame retardant synergist;

[0191] PE wax 0.5 parts;

[0192] Antioxidant 10100.5 parts;

[0193] The preparation method is basically the same as that of Example 1, except that the ingredients and portions of the raw material components are different, see Table 1 and Table 2.

[0194] Comparative Example 6:

[0195] Please refer to Table 1 and Table 2. This comparative example includes the following raw materials in parts by weight:

[0196] ABS resin 60 parts;

[0197] TCP 21 copies;

[0198] PE wax 0.5 parts;

[0199] Antioxidant 10100.5 parts;

[0200] The preparation method is basically the same as that of Example 1, except that the ingredients and portions of the raw material components are different, see Table 1 and Table 2.

[0201] Comparative Example 7:

[0202] Please refer to Table 1 and Table 2. This comparative example includes the following raw materials in parts by weight:

[0203] ABS resin 60 parts;

[0204] MCA 21 copies;

[0205] PE wax 0.5 parts;

[0206] Antioxidant 10100.5 parts;

[0207] Comparative Example 8:

[0208] Please refer to Table 1 and Table 2. This comparative example includes the following raw materials in parts by weight:

[0209] ABS resin 60 parts;

[0210] TCP 8 copies;

[0211] MCA 8 copies;

[0212] 5 parts of benzo[B]naphtho[2,3-D]furan-2-hydroxyboronic acid;

[0213] PE wax 0.5 parts;

[0214] Antioxidant 10100.5 parts;

[0215] Comparative Example 9:

[0216] Please refer to Table 1 and Table 2. This comparative example includes the following raw materials in parts by weight:

[0217] ABS resin 60 parts;

[0218] TCP 8 copies;

[0219] MCA 8 copies;

[0220] 5 parts of aminopropyl heptaisobutyl caged polysilsesquioxane;

[0221] PE wax 0.5 parts;

[0222] Antioxidant 10100.5 parts;

[0223] The preparation method is basically the same as that of Example 1, except that the ingredients and portions of the raw material components are different, see Table 1 and Table 2.

[0224] Comparative Example 10:

[0225] Please refer to Table 1 and Table 2. This comparative example includes the following raw materials in parts by weight:

[0226] ABS resin 60 parts;

[0227] TCP 8 copies;

[0228] MCA 8 copies;

[0229] 1.6 parts of benzo[B]naphtho[2,3-D]furan-2-hydroxyboronic acid;

[0230] 3.4 parts of aminopropyl heptaisobutyl caged polysilsesquioxane;

[0231] PE wax 0.5 parts;

[0232] Antioxidant 10100.5 parts;

[0233] The preparation method is basically the same as that of Example 1, except that the ingredients and portions of the raw material components are different, see Table 1 and Table 2.

[0234] Comparative Example 11:

[0235] Please refer to Table 1 and Table 2. This comparative example includes the following raw materials in parts by weight:

[0236] ABS resin 60 parts;

[0237] TCP 8 copies;

[0238] MCA 8 copies;

[0239] 35 parts of modified POSS flame retardant synergist;

[0240] PE wax 0.5 parts;

[0241] Antioxidant 10100.5 parts;

[0242] The preparation method is basically the same as that of Example 1, except that the ingredients and portions of the raw material components are different, see Table 1 and Table 2.

[0243] Comparative Example 12:

[0244] ABS resin 60 parts;

[0245] TCP 8 copies;

[0246] MCA 8 copies;

[0247] 45 parts of modified POSS flame retardant synergist;

[0248] PE wax 0.5 parts;

[0249] Antioxidant 10100.5 parts;

[0250] The preparation method is basically the same as that of Example 1, except that the ingredients and portions of the raw material components are different, see Table 1 and Table 2.

[0251] The acrylonitrile-styrene-butadiene copolymer materials prepared in the above examples and comparative examples were injection molded into sheets or compression molded sheets, and flame retardancy grade, oxygen index, tensile strength, and cantilever notched impact strength were tested. The test standards are as follows:

[0252] (1) Flame retardant grade test

[0253] The test was conducted according to the UL94 standard, with a sample thickness of 3 mm and a test temperature of 23 ± 2 ° C. Three samples were tested using the UL94 vertical combustion test device of Jiangsu Zhengrui Taibang Electronics Co., Ltd., and any dripping was observed.

[0254] (2) Oxygen index

[0255] According to GB / T 2406.2-2009, the sample size is prepared according to the type IV sample. The test is carried out according to method A-top surface ignition method. The oxygen index of three samples is tested using the oxygen index tester device of Fangshang Analytical Instrument Equipment Factory, Jiangning District, Nanjing, and the results are averaged.

[0256] (3) Tensile strength

[0257] The test was conducted in accordance with Article 9 of GB 1040-2008, the test temperature was 23±2℃, and the tensile test used a standard dumbbell-shaped specimen with a tensile speed of 250mm / min. The tensile strength of three specimens was tested using a micro-controlled electronic universal material tensile machine from Dongguan High-speed Railway Testing Co., Ltd., and the results were averaged.

[0258] (4) Cantilever beam notch impact strength

[0259] The test was carried out according to Type A in GB / T 1843-2008, and the test temperature was 23±2°C. The cantilever beam pendulum impact tester of Guangdong Aisrui Instrument Technology Co., Ltd. was used to test the cantilever beam notched impact strength of three samples, and the results were averaged.

[0260] The test results are shown in Table 3.

[0261] Table 2 Examples of the present invention and comparative examples

[0262]

[0263]

[0264] Table 3 Performance test table of the embodiments of the present invention and comparative examples

[0265]

[0266]

[0267] According to Table 3, it can be seen that the flame retardant properties and mechanical properties of the ABS injection molded sheets of Examples 1-6 are good, the flame retardant grades all reach V0 level, no dripping occurs when the V0 level is tested, the oxygen index is >30%, the tensile strength is >29MPa, and the cantilever notched impact strength is >170J / m, which indicates that the ABS material of the present invention has good flame retardant properties and mechanical properties. It can be seen from Example 5 and Comparative Example 1 that 1 portion of modified POSS flame retardant is too high, and the flame retardant grade is V1, and flame retardant performance is not up to standard, oxygen index decreases, mechanical properties decrease, and tensile strength and cantilever notched impact strength are all reduced; It can be seen from Example 5 and Comparative Example 2 that when modified POSS flame retardant 1 is not added, the flame retardant grade is V2, there is dripping, and flame retardant performance is not up to standard, oxygen index decreases, and cantilever notched impact strength decreases; It can be seen from Example 5 and Comparative Example 3 that when phosphorus-based flame retardant tricresyl phosphate TCP is not added, the flame retardant grade is V2, and flame retardant performance is not up to standard, oxygen index decreases, mechanical properties decrease, and tensile strength and cantilever notched impact strength are all reduced; It can be seen from Example 5 and Comparative Example 4 that when nitrogen-based flame retardant melamine urate (MCA) is not added, the flame retardant grade is V2, there is dripping, and flame retardant performance is not up to standard, oxygen index decreases, and tensile strength Reduced; It can be seen from Example 5 and Comparative Example 5 that when only modified POSS flame retardant 1 is used as a flame retardant, the flame retardant grade is V2, the flame retardant performance is not up to standard, the oxygen index is reduced, and the cantilever notched impact strength is reduced; It can be seen from Example 5 and Comparative Example 6 that when only the phosphorus-based flame retardant tricresyl phosphate TCP is used, the flame retardant grade is V2, there are drippings, the flame retardant performance is not up to standard, the oxygen index is reduced, and the tensile strength is reduced; It can be seen from Example 5 and Comparative Example 7 that when only the nitrogen-based flame retardant melamine urate (MCA) is used, the flame retardant grade is V2, there are drippings, the flame retardant performance is not up to standard, the oxygen index is low, and the cantilever notched impact strength is reduced, which shows that the modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergists have a synergistic flame retardant effect with phosphorus-based flame retardants and nitrogen-based flame retardants, which reduces the amount of various flame retardants while improving the flame retardant and mechanical properties of ABS materials.It can be seen from Example 5 and Comparative Example 8 that the modified POSS flame retardant 1 has improved anti-drip, oxygen index and cantilever notched impact strength compared with the benzo[B]naphtho[2,3-D]furan-2-hydroxyboric acid flame retardant; it can be seen from Example 5 and Comparative Example 9 that the modified POSS flame retardant 1 has improved flame retardancy, anti-drip, oxygen index, tensile strength and cantilever notched impact strength compared with the aminopropyl heptaisobutyl caged polysilsesquioxane flame retardant; it can be seen from Example 5 and Comparative Example 10 that the modified POSS flame retardant 1 has improved anti-drip performance compared with the flame retardant mixed with aminopropyl heptaisobutyl caged polysilsesquioxane and benzo[B]naphtho[2,3-D]furan-2-hydroxyboric acid. , oxygen index, tensile strength and cantilever notched impact strength are all improved; it can be seen from Example 3 and Comparative Example 11 that the flame retardant grade, anti-drip, oxygen index, tensile strength and cantilever notched impact strength of modified POSS flame retardant 1 are improved compared with modified POSS flame retardant 3, i.e., methyl boric acid modified aminopropyl heptaisobutyl caged polysilsesquioxane flame retardant; it can be seen from Example 5 and Comparative Example 12 that the anti-drip performance and oxygen index of modified POSS flame retardant 1 are better than those of modified POSS flame retardant 4, i.e., phenyl boric acid modified aminopropyl heptaisobutyl caged polysilsesquioxane flame retardant, which illustrates that the polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist of the present invention have excellent flame retardant properties.

[0268] The above are only preferred embodiments of the present invention, and do not limit the patent scope of the present invention. For those skilled in the art, the present invention may have various changes and modifications. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the patent protection scope of the present invention.

Claims

1. An acrylonitrile-styrene-butadiene copolymer material, characterized in that: The raw materials of the acrylonitrile-styrene-butadiene copolymer material include, by weight: 50-70 parts of acrylonitrile-styrene-butadiene copolymer, Phosphorus flame retardant 5-10 parts, 5-10 parts of nitrogen flame retardant, 2-8 parts of modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist, Wherein, the structure of the modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist is: Wherein, R is a non-reactive group, such as isobutyl, isooctyl, ethyl, cyclohexyl, cyclopentyl, or phenyl, and R1 is n-propyl or phenylene; R2 is a cyclic structure with a carbon-to-hydrogen ratio greater than 1, including at least one of a benzofuran group and a polycyclic aromatic group.

2. The acrylonitrile-styrene-butadiene copolymer material according to claim 1, characterized in that: The benzofuran group includes at least one of a benzofuran group and a dibenzofuran group; And / or, the polycyclic aromatic group includes at least one of a naphthalene ring group, an anthracene ring group, a phenanthrene ring group, an acenaphthene ring group, a fluorene ring group and a perylene ring group.

3. The acrylonitrile-styrene-butadiene copolymer material according to claim 1, characterized in that: The modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist is prepared by dehydration reaction of compound 1 and compound 2 under the action of a catalyst, and the reaction route is as follows:

4. The acrylonitrile-styrene-butadiene copolymer material according to claim 3, characterized in that: The molar ratio of compound 1 to compound 2 is 2:

1.

5. The acrylonitrile-styrene-butadiene copolymer material according to claim 3, characterized in that: The preparation method of the modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist comprises the following steps: Dissolving compound 1 in an organic solvent, adding an aqueous solution of compound 2 under the action of a catalyst, performing a catalytic reaction, and then washing and drying to obtain the modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist; Wherein, the organic solvent includes at least one of alcohols, aromatic hydrocarbons, aliphatic hydrocarbons, alicyclic hydrocarbons, ethers, ketones and diol derivatives; The catalyst includes at least one of an acidic catalyst, a metal catalyst, and a basic catalyst.

6. The acrylonitrile-styrene-butadiene copolymer material according to claim 1, characterized in that: The phosphorus-based flame retardant includes at least one of phosphate ester and phosphite ester.

7. The acrylonitrile-styrene-butadiene copolymer material according to claim 6, characterized in that: The phosphate flame retardant includes at least one of tris(β-chloroethyl) phosphate, tributyl phosphate, triphenyl phosphate, and dimethyl methyl phosphate; the phosphite flame retardant includes at least one of diisopropyl ether diphenyl phosphite, triisoquinoline phosphite, triphenyl phosphite, dimethyl phosphite, and diethyl phosphite.

8. The acrylonitrile-styrene-butadiene copolymer material according to claim 1, characterized in that: The raw materials of the acrylonitrile-styrene-butadiene copolymer material also include at least one of a lubricant and an antioxidant; wherein, in terms of weight, the lubricant is 0.2-1 parts, and the antioxidant is 0.5-2 parts; And / or, the nitrogen-based flame retardant includes at least one of melamine urate, melamine phosphate, melamine inorganic acid salt, dicyandiamide, and melamine.

9. A method for preparing the acrylonitrile-styrene-butadiene copolymer material according to claim 1, characterized in that: The method comprises the following steps: mixing the raw materials uniformly, extruding and granulating through an extruder, and obtaining granular materials, namely the acrylonitrile-styrene-butadiene copolymer material.

10. The method for preparing acrylonitrile-styrene-butadiene copolymer material according to claim 9, characterized in that: The raw material also includes at least one of a lubricant and an antioxidant; And / or, the extruder is a twin-screw extruder, and the processing temperatures of each temperature zone of the extruder are: zone 1 140-160°C, zone 2 170-180°C, zone 3 190-200°C, zone 4 190-200°C, zone 5 190-200°C, zone 6 190-200°C, zone 7 190-200°C, zone 8 170-190°C, die head 200-210°C, screw speed 150-170r / min.

Citation Information

Patent Citations

  • Phosphorus-based synergistic flame-retardant ABS (acrylonitrile-butadiene-styrene) composite material and preparation method thereof

    CN103289290A

  • Silsesquioxane complex polymer and method for preparing same

    CN106029747A

  • Preparation method of low-smoke and high-modulus PC / ABS alloy halogen-free flame-retardant material and phosphorus-silicon-containing flame retardant

    CN118909260A

  • Additive phosphorus-containing polysiloxane compound for thermosetting resins, flame retardant composition comprising same, and articles made therefrom

    US20200291232A1

  • Flame-retardant ABS resin and process for producing the same

    WO2005035604A1